Tectonostratigraphic evolution of the Orphan Basin and Flemish Pass region – Part 2: Regional structural development and lateral variations in rifting style. (November 2021) - Cawood, Adam J.; Ferrill, David A.; Morris, Alan P.; Norris, David; McCallum, David; Gillis, Erin; Smart, Kevin J.
Abstract: Interpretation of newly acquired modern broadband seismic reflection data and structural restoration of three regional, WNW-ESE oriented cross-sections across the Orphan Basin, Flemish Pass and Flemish Cap provide new insights into rift evolution and structural style in the area. Our results show that regional extension in the Orphan Basin and Flemish Pass area largely occurred between 170 Ma and 135 Ma, and later extension (135 Ma onwards) in the study area was accommodated east of Flemish Cap. Seismic stratigraphic mapping provides evidence for significant thicknesses of Jurassic strata throughout the Orphan Basin and Flemish Pass area, and structural interpretations highlight the importance of crustal-scale extensional detachment faults in controlling the geometry and position of Jurassic sub-basins at a range of scales. Stacked detachment surfaces and coincident extreme crustal attenuation (to ca. 3.1 km) are observed in eastern parts of the Orphan Basin in an area defined in this study as the Orphan Trough. Rifting style in the central, northern, and eastern parts of the Orphan Basin is dominated by low-angle detachment faulting with maximum extension perpendicular to the incipient rift axis. In contrast, structural geometries in the southwestern part of the basin are suggestive of transtensional deformation, and interplay of normal and strike-slip faulting. Results from map-based interpretation show that strike-slip faults within this transtensional zone are associated with displacement transfer between half-grabens of opposing polarity, rather than regional strike-slip displacement. These structures are interpreted as contemporaneous and kinematically linked to displacement along low-angle detachment surfaces elsewhere and are not attributed to distinct episodes of oblique extension. Highlights: Regional structural characterization of the Orphan Basin - Flemish Pass – Flemish Cap region. Kinematic restoration and crustal area balancing of three laterally compatible, regional cross sections. A single phase of protracted rifting from ca. 170 Ma to 135 Ma is interpreted in the Orphan Basin and Flemish Pass region. Hyperextension, crustal-scale detachment surfaces and crustal attenuation associated with rift development. Transtensional deformation in the southern part of the Orphan Basin compatible with rift-related extension.